STUDY OF GENETIC DIVERSITY AMONG SIX IRAQI WHEATGENOTYPES USING RANDOM AMPLIFIED POLYMORPHIC DNA - Salo, Wisam; Nasir, Gulboy (Iraqi Journal of Science, 2024)
The degree of genetic divergence was estimated in six Iraqi soft wheat genotypes,four exotic genotypes, one produced by hybridization and one produced by gammairradiation, through random amplified polymorphic DNA methodology. A total of42 DNA fragments were generated by the 3 random primers, with an average ofabout 7.4 bands per primer. The 42 fragments showed polymorphism among the sixwheat genotypes. Jaccard similarity matrix ranged from 25 to 66.7%, whichindicated a high genetic diversity among the genotypes. We conclude that randomamplified polymorphic DNA analysis can be used for the characterization andgrouping of wheat genotypes; these results will be helpful in our wheat breedingprogram.